Application of the Precautionary Principle of Notary in Making Authentic Deed Against the Use of False Identity - Nandila Puspavidya Safitri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The increase in cases of identity forgery in notarial deeds is due to the lack of caution and thoroughness on the part of the notary regarding the identity submitted by the confrontants, thus providing opportunities for other parties who have bad intentions to manipulate information. The occurrence of identity forgery cases shows that the notary lacks careful and thorough examination of the information provided by the notary. Weaknesses in the identity verification process can result in the cancellation of the deed and harm the parties involved in the agreement, including the notary as the deed maker. Based on Decision Number 140/PDT/2020/PT.DKI dated 20 April 2020 jo. Decision of the North Jakarta District Court Number 101/Pdt.G/2015/PN.Jkt.Utr explained that there was a case of identity forgery committed by the confronter in making an authentic deed. Based on this background, the main problems to be discussed can be formulated, namely: How is the application of the precautionary principle in carrying out the office of Notary against the confronter who uses a fake identity? Can the notary be held accountable for this? The research method used is normative juridical, the approaches used in this writing are: Statute Approach and Conceptual Approach. The application of the precautionary principle in recognising the confronters, namely the Notary conducts an introduction to the identity of the confronters, verifies carefully the subject and object data, checks the documents directly or online to the relevant government agency system. The legal consequences of Notaries who are proven not to apply the precautionary principle in recognising the faces can be subject to administrative sanctions in accordance with the Notary Position Law.